2015
DOI: 10.1007/s12079-015-0303-9
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine and phenytoin induce matrix synthesis, but not proliferation, in intact human gingival connective tissue ex vivo

Abstract: Drug-induced gingival enlargement (DIGE) is a fibrotic condition that can be caused by the antihypertensive drug nifedipine and the anti-seizure drug phenytoin, but the molecular etiology of this type of fibrosis is not well understood and the role of confounding factors such as inflammation remains to be fully investigated. The aim of this study was to develop an ex vivo gingival explant system to allow investigation of the effects of nifedipine and phenytoin alone on human gingival tissue. Comparisons were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
0
5
0
1
Order By: Relevance
“…Providing evidence that FAK and JNK are downstream mediators of periostin induction of fibronectin and type I collagen expression in human gingival fibroblasts, it opens the intriguing possibility that periostin based biomaterials could be used, clinically, as a means of stimulating matrix synthesis during gingival healing [15]. It also provides insights into the pathology of DIGE, an inflammatory condition which we have shown is associated with overexpression of periostin [117][118][119]. Induction of matrix synthesis in the presence of periostin would also partially explain the overgrowth of gingival tissue associated with the condition.…”
Section: Gingival Fibroblasts and Jnkmentioning
confidence: 83%
See 1 more Smart Citation
“…Providing evidence that FAK and JNK are downstream mediators of periostin induction of fibronectin and type I collagen expression in human gingival fibroblasts, it opens the intriguing possibility that periostin based biomaterials could be used, clinically, as a means of stimulating matrix synthesis during gingival healing [15]. It also provides insights into the pathology of DIGE, an inflammatory condition which we have shown is associated with overexpression of periostin [117][118][119]. Induction of matrix synthesis in the presence of periostin would also partially explain the overgrowth of gingival tissue associated with the condition.…”
Section: Gingival Fibroblasts and Jnkmentioning
confidence: 83%
“…Myofibroblast differentiation has been postulated to be an important cellular transition in gingival wound healing, although we recently reported that α-SMA positive myofibroblasts are absent during gingival healing in a rat model [15] and we have previously shown that myofibroblasts are not associated with drug-induced gingival enlargement (DIGE), a fibrotic condition of the gingiva [117][118][119]. TGFβ1 has been shown to induce myofibroblast differentiation through canonical and noncanonical signaling [120][121][122].…”
Section: Gingival Fibroblasts and Jnkmentioning
confidence: 99%
“…Three specific TGF-β isoforms have been identified, with specific differences in their role in wound healing particularly in skin [ 37 ]. Indeed, much work on TGF-β isoforms in gingival tissue relates to drug-induced gingival enlargement, which is associated with increased ECM production [ 38 ], but α-SMA upregulation [ 39 , 40 ]. TGF-β1 is considered to be pro-fibrotic and some evidence suggests that TGF-β3 is anti-fibrotic, although the latter remains somewhat controversial with conflicting results in the literature [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in parallel with Kantarci et al, [41] who reported reduction of apoptosis in fibroblasts rather than proliferation due to decreased inflammation attained by phenytoin action. Furthermore, Kim et al, [42] reported that phenytoin did not significantly increase proliferation of c.t cells, and suggested that PIGE was only due to increased matrix deposition.…”
Section: Less Anti-pcna Expression In Epithelial Cells In Groupmentioning
confidence: 99%